Serum KLF5 and CXCL12 levels in patients with chronic obstructive pulmonary disease complicated with type II respiratory failure: Serum KLF5 and CXCL12 levels in COPD with II-RF - Liu, Fangfang; Wang, Na; Sun, Ruru; Fu, Songmin; Chen, Yi; Dong, Pingping (Journal of Medical Biochemistry, 2026)
[Objective] To explore the changes in the serum levels and significance of Kruppel-like factor 5 (KLF5) and chemokine ligand 12 (CXCL12) in individuals suffering from type II respiratory failure (II-RF) in conjunction with an acute exacerbation of chronic obstructive pulmonary disease (AECOPD).[Methods] The observation group consisted of 164 patients with AECOPD and II-RF who were admitted to the hospital between January 2022 and January 2025.  There were two groups of patients in the observation group: one with a good prognosis and another with a bad prognosis. The control group consisted of an additional 90 healthy people who were examined physically in the hospital throughout that time. The levels of serum KLF5 and CXCL12 in all research subjects were determined via enzyme-linked immunosorbent assay (ELISA). The associations between the blood levels of KLF5 and CXCL12 in patients with AECOPD combined with II-RF and the associated lung function indicators and the Acute Physiology and Chronic Health Evaluation II (APACHE II) score were examined using Pearson correlation analysis. The predictive value of serum KLF5 and CXCL12 for the prognosis of patients with AECOPD combined with II-RF was analyzed.[Results] Serum KLF5 and CXCL12 levels were substantially higher in the observation group than in the control group (P
Keywords: Chronic obstructive pulmonary disease; Kruppel-like factor 5; Chemokine ligand 12; Respiratory failure; Acute exacerbation period